Exploring strategy : text and cases - Whittington, Richard, 1958-; Regnér, Patrick; Angwin, Duncan; Johnson, Gerry; Scholes, Kevan (Pearson, 2020)
Exploring Strategy, 12th Edition, by Whittington, Angwin, Regner, Johnson and Scholes has long been the essential introduction to strategy for the managers of today and tomorrow and has sold over one million copies worldwide. From entrepreneurial start-ups to multinationals, charities to government agencies, this book raises the big questions about organisations how they prosper, how they grow, how they innovate and how they change. Text and Cases also provides a wealth of extra case studies written by experts in the subject to aid and enrich your understanding. Examples are taken from events and organisations as diverse as Adnams, Siemens, Air Asia, Apple, Handelsbanken, Glastonbury and the Indian Premier League.